Effect of 17β-trenbolone exposure during adolescence on the circadian rhythm in male mice. (February 2022) - Zhang, Shaozhi; Feng, Xizeng
Abstract: The suprachiasmatic nucleus (SCN) is the main control area of the clock rhythm in the mammalian brain. It drives daily behaviours and rhythms by synchronizing or suppressing the oscillations of clock genes in peripheral tissue. It is an important brain tissue structure that affects rhythm stability. SCN has high plasticity and is easily affected by the external environment. In this experiment, we found that exposure to the endocrine disruptor 17β-trenbolone (17β-TBOH) affects the rhythmic function of SCN in the brains of adolescent male balb/c mice. Behavioural results showed that exposure to 17β-TBOH disrupted daily activity-rest rhythms, reduced the robustness of endogenous rhythms, altered sleep-wake-related behaviours, and increased the stress to light stimulation. At the cellular level, exposure to 17β-TBOH decreased the c-fos immune response of SCN neurons to the large phase shift, indicating that it affected the coupling ability of SCN neurons. At the molecular level, exposure to 17β-TBOH interfered with the daily expression of hormones, changed the expression levels of the core clock genes and cell communication genes in the SCN, and affected the expression of wake-up genes in the hypothalamus. Finally, we observed the effect of exposure to 17β-TBOH on energy metabolism. The results showed that 17β-TBOH reduced the metabolic response and affected the metabolic function of the liver. This study revealed the influence of environmental endocrine disrupting chemicals (EDCs) on rhythms and metabolic disorders, and provides references for follow-up research. Graphical abstract: Image 1 Highlights: Exposure to 17β-TBOH disrupted the activity-rest rhythm and reduced the robustness of the endogenous rhythm in mice. Exposure to 17β-TBOH changed the sleep-wake related behaviours and increased the stress to light stimulation in mice. Exposure to 17β-TBOH affected the coupling ability of SCN neurons in mice. Exposure to 17β-TBOH reduced the metabolic capacity and affected the metabolic function of the liver in mice.